The Great Commission you and the Muslims - Nehls, Gerhard (SIM International Life Challenge, 1988)
Includes bibliographical references.
Prequel to "Christians answer Muslims" and "Christians ask Muslims", which see also.
Keywords: Missions to Muslims; Christianity and other religions -- Islam